Lucrecia Martel and Albertina Carri: subjective feminine narratives in the nuevo cine argentino (NCA) - Campo, Mônica Brincalepe (História: Questões e Debates, 2018)
Lucrecia Martel and Albertina Carri are two of the most important directors of the nuevo cine argentino (new argentinian cinema), a cinematographic movement starting from the 1990s and enduring through the XXI century. In their works, subjectivity is developed as a feature that underlines private themes, being particu-larly connected to women’s outlook on the family relations, social structures and cultural practices that surround them. From a sensitive view on personal matters, they then develop a sharp and attentive critique of their environment. This empha-sis in subjectivity strives to understand how the point of view of the narratives af-fects the writing of history and expresses the present time. Inventive use of lan-guage and audiovisual possibilities mark the production of these directors and construct their specificities as artists. The themes of conflict stand out in their works, both those referring to violence existing inside of families and those relat-ed to daily life in society, instigating the viewers to think about the singularity of those clashes as contemporary expressions in our history. In this article, two mov-ies will be analyzed: Los Rubios, from Albertina Carri (2003), e La mujer sin cabe-za, from Lucrecia Martel (2008).